Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Penghindaran Pajak Pada Perusahaan Pertambangan yang Terdaftar di BEI - Puja Raihani, Puja Raihani; Muhammad Salman; Tuti Meutia (Journal Research of Economic and Bussiness, 2024)
This research aims to examine the effect of: (1) profitability on tax avoidance, (2) firm size on tax avoidance, (3) leverage on tax avoidance, (4) profitability, company size and leverage on tax avoidance simultaneously. This research is a quantitative research with the population in this research being 87 energy sector mining companies listed on the IDX, and a sample of 8 companies. The data analysis technique in this research uses descriptive statistical tests, classical assumption tests, t tests, simultaneous tests and determination tests (R2). The results of the t test for the profitability variable have a value of 0,004<0,05, which means that the profitability variable has a significant influence on tax avoidance.  The company size variable has a value of 0,000<0,05 which means that the company size variable has a significant influence on tax avoidance. The leverage variable has a value of 0.771 > 0.05, which means that the leverage variable does not have a significant influence on tax avoidance. The results of the F test obtained a value of 0.000 < 0.05, indicating that the variables used in this research simultaneously have a significant effect on tax avoidance. From the results of the coefficient of determination test, it was found that 30,3% of the dependent variable could be explained by the independent variable, while the remaining 69,7% was influenced by other factors not included in this research.